Butte Paper - Increasing the Efficiency of MacDougall Roasters at the Great Falls Smelter of the Anaconda Copper Mining Co. - Frank R. Corwin; Selden S. Rodgers (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1914)
PAGE I. Introduction,........... 383 11. Brief History of Present MacDoUgall Plant,.... 384 III. First Experimental Work on Increasing Capacity of Furnaces, 385 IV. Effect On MacDouRall Plant of IncreaBed Draft from New Smelter Stack,,.......... V. Increasing the Capacity of the MacDouGall FurnaceS,.. 391 (A). Test of Arthur Crowfoot on Increasing Capacity,.... (a). Description of Test,........ (6). Discussion of Results Obtained from Test,... 393 (B). Investigation Carried Out by John A. Church, Jr.,... 395 (a). Advantages of High Speed,......398 (C). Effect on Regular Operation of Department by Applying Results Obtained from Experimental Work ..... 399 (D). Fundamental Principles Involved in Increasing the Tonnage, . 400 VI. Treatment of an INcreased Amount of Ore Screenings,.. 401 VII. Maximum Percentage oF Ore Screenings in a MacDoUGall Feed, 403 VIII. Tests to Further Increase Capacity of Furnaces,... 406 IX. Tests to Decrease PercentaGe of Flue Dust made by MacDouGall Furnaces,............. (A). Repath-Marcy Furnace......... 408 (B). Modified Hepath-Marcy Furnace,....... (C). Crouse Furnace Designed for Dust Prevention,.... 413 (a). Tests on Crouse Furnace,....... X. Concrete Hearths,.......... 419 XI. Conclusion,............ I. Introduction. Since the first installation of MacDougall roasters at the Great Falls smelter of the Anaconda Copper Mining Co., the capacity of the furnaces.has been more than doubled. During the first nine or ten years of the operation of the MacDougall department the tonnage treated by the furnaces remained practically unchanged. Experimental work carried out in 1906, however, showed that increasing the draft of the furnaces would bring about an increase in capacity. In 1909 the MacDougall department was connected to the new smelter stack and